Phosphorous-Nitrogen flame retardants engineering MXene towards highly fire safe thermoplastic polyurethane. (January 2022) - Liu, Chuan; Yang, Dong; Sun, Mengnan; Deng, Guojun; Jing, Binghao; Wang, Ke; Shi, Yongqian; Fu, Libi; Feng, Yuezhan; Lv, Yuancai; Liu, Minghua
Abstract: Developing high-performance polymeric materials with highly effective flame retardancy and the generation of ultra-low toxic fumes in a fire remains an intractable challenge. In this work, a novel titanium carbide-polyphenyl phosphate ester amide hybrid (Ti3 C2 Tx -PPPA) was synthesized via the esterification and hydrogen bonding induced assembly for fabrication of thermoplastic polyurethane (TPU) nanocomposites. The Ti3 C2 Tx -PPPA displayed strong interface interaction with TPU matrix. The cone calorimetry results indicated that the total heat release, total smoke release and total carbon monoxide yield of the TPU nanocomposite with 1.0 wt% Ti3 C2 Tx -PPPA were dramatically decreased by 32.6%, 54.4% and 36.8%, respectively, compared to those of pristine TPU. Besides, TPU/Ti3 C2 Tx -PPPA-1.0 showed the highest Flame Retardancy Index (1.76) among all the specimens. The improved fire safety of TPU was ascribed to the catalytic charring, the chemical transformation and the barrier effect of the Ti3 C2 Tx nanosheets and PPPA trapping free radicals. This work provides a promising strategy for significantly improving the fire-resistance of TPU and further widening its industrial application. Graphical abstract: Image 1 Highlights: Ti3 C2 Tx -PPPA was prepared by hydrogen bonding induced assembly of Ti3 C2 Tx and PPPA. Ti3 C2 Tx -PPPA hybrid showed strong interface interaction with TPU matrix. TPU/Ti3 C2 Tx -PPPA nanocomposites exhibited markedly reduced total smoke release and total CO yield. Decreases are due to multiple charring, barrier and quenching effect of Ti3 C2 Tx -PPPA hybrid.